NEMAWASHI: STUDI KASUS RENCANA KERETA CEPAT (SHINKANSEN) DI INDONESIA - Dewi, R. Sonnya Heliantina Dewi (Media Bahasa, Sastra, dan Budaya Wahana, 2016)
AbstractThe Japanese Industries has already known around the world, especially the automotives industries. This paper described how Japanese still brings all of the old cultural values such as oyagokoro, amae, shinyo, enryo, uramu and nemawashi through the latest high-end technolo- gies. A case study of Indonesia’s the first-ever high-speed project that excluded Japan from its de- velopment plan. Japan considered taking action as wise as they could while facing the government of Indonesia’s decision with their traditional cultural values. However, this issue has affected the relationship between Indonesia and Japan. Keyword: Japan, high-speed train, oyagokoro, amae, nemawashi